Hubungan antara ketagihan internet dengan kegelisahan dan kemurungan di kalangan pelajar sekolah menengah di daerah Kluang - Tan, Lem Beng (2021)
Internet addiction and its association with psychological risk has become a critical phenomenon globally as well as in Malaysia, especially among adolescents. Given this critical issue the researchers conducted a study to identify the relationship between internet addiction with anxiety and depression among high school students. This study was conducted to identify the level of internet addiction according to the age range in the age range of 13 to 18 years. The study sample consisted of 126 students from secondary schools in Kluang District. This study was conducted to identify the level of internet addiction according to the age range in the age range of 13 to 18 years. The study sample consisted of 126 students from secondary schools in Kluang District. The objective of this study is to identify the level of internet addiction, the level of anxiety and the level of depression among secondary school students in Kluang District. The next objective aims to identify the relationship between these three variables. The design of this study was descriptive with correlation method. The instruments used were in the form of questionnaires with the Internet Addiction Test by Kimberly Young (1998), the Beck Depression Inventory (BDI) and the Beck Anxiety Inventory (BAI) created by the renowned American psychologist Aaron T. Beck. Data were analyzed using Statistical Package for Social Science (SPSS Version 23) software that is Spearman Correlation test. The findings of the study showed that 59 respondents (46.8%) were regular internet users, 58 respondents (46%) were at a low level, 8 respondents (6.3%) were at a moderate level, while 1 respondent (0.8%) was at a high level of internet addiction. height. The findings of the study showed that respondents who used time to surf the internet less than one hour a day were 4 people (3.2%), while 2 to 4 hours were 17 people (13.5%), while respondents who spent more than 5 hours were 49 people (38.9) %), and 56 people (44.4%) use the internet at any time. Based on the findings of the study, a total of 17 respondents 13.5 (%) did not have symptoms of anxiety, a total of 109 respondents (86.5%) were at a low level of anxiety, while no respondents (0%) were at a high level of anxiety. The findings of the study showed that 58 respondents (46%) were at a low level of depression, 8 respondents (6.3%) were at a moderate level of depression, while 1 respondent (0.8%) was at a high level of depression, and 59 (46.8%) respondents did not exist. depressive symptoms. The findings showed that there was a significant relationship between internet addiction with anxiety (r = 0.309) and depression (r = 0.400). In conclusion, the results show that there is a correlation between the variables of internet addiction, anxiety and depression among secondary school students in Kluang District. The findings of the study can be used as a guide on behalf of researchers, adolescents, family members and the community. This study allows researchers to gain experience to examine the phenomenon of society in a scientific way, and be a guide to adolescents, family members and society to combat social symptoms faced by adolescents who fall into internet addiction. Keywords: internet addiction, anxiety, depression.